A Review of the Importance on the Need of Micro Medical and Health Takaful - Fauzilah, Salleh; Ahmad Shukri, Yazid; Wan Norhayate, Wan Daud; Norizan, Remli; Puspa Liza, Ghazali; Nahidah, Mustafa (2017)
The overall aim of this paper is to discuss health care expenses incurred and borne by the government as well as the citizens. The development of Medical and Health Insurance (MHI) / Medical and Health Takaful (MHT) in Malaysia has also been reviewed accordingly in this study. Moreover, the issues and challenges raised in regard to the implementation of Health Takaful in Malaysia has been thoroughly assessed by focusing on low to moderate level individuals, specifically the hard-core poor, poor and low (B40), and moderate-income earners (M40). Therefore, the aims of the paper is to present the views of scholars on the importance of micro medical and health Takaful in daily life and to recommend framework of micro medical and health Takaful for poor people in Malaysia.